A case study on implementation of just-in-time (JIT) production system in Malaysia automotive industry - Nurul Fateha, Abd Aziz (2012)
This thesis deals with production system and management used in automotive industry. Just-In-Time (JIT) production system is originates from Japan and claimed as one of the best production system that leads Toyota Motor Corporation (TMC) as one of the best car manufacturer in the world. Even there have been a lot of studies related to JIT production system in automotive industry globally; there is still lack of evidence that Malaysia automotive industry is practicing this remarkable production system. Because of that, this study conducted to explore and figure out on JIT implementation in Malaysia automotive industry. This study started on reviewing elements suggested by literature that are considered important to ensure the successfulness of JIT implementation in an organization. These identified elements then used in investigation of JIT implementation in Malaysia automotive industry. A set of questionnaire designed based on activities that related to elements figured in order to further investigate of JIT implementation in an organization. This questionnaire then distributed randomly to automotive companies all over Malaysia. All data then collected and tested by using a well-known statistical test, a Chi-Square test. Chi-Square test used to find the relationship between elements and activities with types of industry practices in Malaysia automotive industry. These elements are then analyzed and decided either independent or dependent on types of industry. The findings are then summarized with some recommendations suggested to automotive company that is planning to implement JIT in their organization.